Volume 3: Coal, Biomass and Alternative Fuels; Combustion and Fuels; Oil and Gas Applications; Cycle Innovations 1994
DOI: 10.1115/94-gt-415
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Technologies for Nuclear Gas Turbine (GT-MHR) Power Conversion System

Abstract: Since the onset of gas-cooled reactor work, almost half a century ago, the potential for direct coupling of a nuclear heat source with a gas turbine power conversion system was recognized, however, the technologies for the realization of this were not available, and the plants operated to date have used Rankine steam turbine power conversion systems. In the early 1990s, technology transfer from the gas turbine and aerospace industries, now make possible the introduction of the gas turbine modular helium reacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…As mentioned by McDonald (1977McDonald ( , 1994aMcDonald ( , I994b, 1995 fig. 5 indicates that it is possible to achieve thermal efficiencies near 50%, remarkably greater than those of nuclear plants with water cooled reactors or liquid metal cooled reactors (General Atomic, 1993).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…As mentioned by McDonald (1977McDonald ( , 1994aMcDonald ( , I994b, 1995 fig. 5 indicates that it is possible to achieve thermal efficiencies near 50%, remarkably greater than those of nuclear plants with water cooled reactors or liquid metal cooled reactors (General Atomic, 1993).…”
mentioning
confidence: 89%
“…Past studies of CCGT systems concentrated on matching closed cycle systems with gas-cooled reactors for nuclear applications (McDonald, 1977(McDonald, , 1994a(McDonald, , 1994bYan and Lidslcy, 1993) and on space or underwater systems (ICoraldanitis et al, 1993(ICoraldanitis et al, , 1994Massardo, 1993;Massardo and Amulfi, 1992). Beyond these applications, where CCGT are indispensable, two other terrestrial CCGT applications are presently dominant.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have been performed, at about 10 year intervals over the last 50 years, and each concluded that a viable project could not be undertaken because of lack of technology readiness. Alas, in the mid 1990s, when it was felt that all of the enabling technologies were in place (McDonald, 1994a) there was no market for this, or any other type of nuclear power plant in the U.S. Work on gas cooled reactors had previously been abandoned in the U.K., France, and Germany, and finally discontinued in the U S with the cessation of funding by the U.S. Government in 1995. At the close of this program the estimated R&D cost to make the concept a reality was on the order of half a billion dollars.…”
Section: Nuclear Gas Turbine Backgroundmentioning
confidence: 99%
“…Today, that situation-is over since the key technologies, developed for other applications, are now available, and by bringing together the various elements described below, the perceived risks of coupling a nuclear reactor with a gas turbine prime-mover have essentially been overcome, although a significant development effort is still necessary. The key enabling technologies have been discussed previously (McDonald, 1994a) and they are summarized below.…”
Section: State-of-the Artmentioning
confidence: 99%